Pulse-Controlled Amplification–A new powerful tool for on-site diagnostics under resource limited conditions - Müller, Katharina; Daßen, Sarah; Holowachuk, Scott; Zwirglmaier, Katrin; Stehr, Joachim; Buersgens, Federico; Ullerich, Lars; Stoecker, Kilian (PLOS Neglected Tropical Diseases, 2021)
Author summary Rapid and reliable on-site diagnostics are an essential part of infectious disease outbreak response and the fight against neglected tropical diseases. In this respect, molecular diagnostics represents the current gold standard. However, the vast majority of current molecular diagnostic methods (such as Polymerase Chain Reaction) are lab-bound techniques, require expensive and heavy instrumentation and are time consuming to perform. Moreover, in resource limited countries with little or no infrastructure, samples often have to be transported over long distances to the few reference laboratories capable of such diagnostics. This significantly slows down the entire diagnostic process, thus considerably delaying important decisions necessary to contain outbreaks and to initiate medical countermeasures. Until now, there are only few rapid on-site diagnostic tests for a limited number of infectious agents available and they often lack sensitivity and/or specificity. Here we present a new technology–pulse-controlled amplification–which enables rapid (<20minutes) and portable, yet sensitive and specific on-site molecular diagnostics based on nucleic acid amplification. The device we developed is lightweight, battery operated and we demonstrate that our tests can be performed under resource limited conditions and without nucleic acid extraction, even when wearing full personal protective equipment. Thus, molecular diagnostics can be carried out on-site in a non-laboratory environment without the need for nucleic acid extraction. We envision that this new technology has the potential to become a gold standard method in nucleic acid detection for front-line and in-field applications.